Penggunaan software Turn It In untuk mendeteksi tindakan plagiarisme - Ulpah Andayani (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2017)
This paper discusses the use of anti-plagiarism checker application (Turnitin) as a toolthat can be used to detect the similarity of a scientific work with other scientific works.The utilization of this software can display the level of percentage of similarity of a workand show the authen-ticity of a writing. The use of this application can further assistthe University in preventing the possibility of plagiarism behavior committed byacademics and university scholars. The utilization of this application can alsoencourage the improvement of the scientific publication produced by the University’sacademicians.